2001
DOI: 10.1103/physreve.64.011602
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theories and molecular simulations of adsorption and phase transitions in nanopores

Abstract: The nonlocal density functional theory (NLDFT) of confined fluids is tested against Monte Carlo simulations by using the example of Lennard-Jones (LJ) fluid sorption in slit-shaped and cylindrical nanopores ranging from 0.3 to 10 nm in width. The fluid-fluid and solid-fluid parameters of the LJ potentials were chosen to represent several experimentally important adsorption systems: nitrogen and carbon dioxide in activated carbons, zeolites, and mesoporous molecular sieves of the MCM-41 type. Freezing in nanopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
220
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 307 publications
(238 citation statements)
references
References 92 publications
11
220
0
7
Order By: Relevance
“…Ravikovitch et al have reported values of 0.202 kcal/mol for and 4.058Å for r 0 for a LJ CM-CM model without charges [44]. The is higher than ours, while the r 0 is smaller, but in reasonable agreement taking into account that they were acquired via very different methods.…”
Section: N 2 Dimersupporting
confidence: 40%
“…Ravikovitch et al have reported values of 0.202 kcal/mol for and 4.058Å for r 0 for a LJ CM-CM model without charges [44]. The is higher than ours, while the r 0 is smaller, but in reasonable agreement taking into account that they were acquired via very different methods.…”
Section: N 2 Dimersupporting
confidence: 40%
“…Some theoretical approaches are able to deal with the complexity of the adsorption phenomenon: molecular simulation methods like the Grand Canonical Monte-Carlo method (GCMC) [3] which is based on an equilibrium statistical treatment of the system or the density functional theory (DFT) [4] which is an approximate statistical mechanics method.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the gas-liquid phase transition in pores (capillary condensation) is a very interesting feature, which is observed when condensable gases are confined in small cavities. The phenomenon has been extensively studied in pores of various geometries both experimentally and theoretically (Evans & Tarazona, 1984 ;Ravikovitch et al, 2001 ;Nilson & Griffiths, 1999 ;Neimark et al, 2003). Capillary condensation takes place at pressures below the bulk condensation pressure at a given temperature.…”
Section: (B) Carbon Dioxide Adsorptionmentioning
confidence: 99%